IMPROVING STUDENTâS SPEAKINGABILITY THROUGH COMMUNICATIVE LANGUAGE GAMES - Irawati, Iisrohli (MAGISTRA, 2014)
One skill that learned in learning and teaching english is Speaking. There are some problems in the teaching and learning speaking class. The problems can be from both sides the teachers or the students. Both are interrelated to each other. The first problems come from the teacher. It is closely related to the method or teaching technique, media, and the material that the teachers use. It is important to apply a technique appropriately in presenting an instructional material in order that the students will be more interesting, active, and motivated in learning speaking. The fact shows that the teachers still find difficulties providing their teaching techniques and strategy. One of the strategy can be used is communicative language games.